ANALYSIS OF SELF-CONFIDENCE LEVELS AMONG ELEMENTARY SCHOOL CHILDREN IN BERAU REGENCY - Santi (Universitas Negeri Surabaya, 2026)
Background: The elementary school years constitute a critical period for the development of competence, aligning with the psychosocial stage of